Studi Deskriptif Kontribusi Pemulung dalam Pengurangan Sampah di TPA Alak Kota Kupang - Meylani Anthonesthe Claudya Massi; Agus Setyobudi; Mustakim Sahdan; Marylin Susanti Junias (Yayasan Literasi Sains Indonesia, 2025)
The Alak Final Disposal Site (TPA) is the only landfill in Kupang City. It has been operating since 1998 and covers an area of 9.14 hectares. The Alak landfill has operated for over 20 years and uses the controlled landfill method in its waste disposal operations. Scavengers are part of the waste management ecosystem at the landfill and play a role in waste reduction by sorting and collecting recyclable materials, thereby helping to reduce the overall waste burden at the site. This study aims to examine the contribution of scavengers in reducing waste at the Alak landfill in Kupang City. The research method used is a quantitative descriptive analysis. The sample consisted of all active scavengers at the Alak landfill from 35 households. The sampling technique used was total sampling, where the entire population that met the criteria was included in the study. The research was conducted for 8 days. Results showed that the most frequently collected waste at the Alak landfill was plastic waste with 2023.85 Kg from the total waste collected. Cans follow as the second most common type of waste with a total of 658.05 kg, cardboard waste amounts to 381 kg, scrap metal to 334.03 kg, and used tires to 187.5 Kg. Scavengers contribute to reducing waste at the Alak landfill around 1.92 % of the total waste entering the landfill each day.